Indonesia on Palestinian Destiny: Perspectives from the Government and Scholars - Andriansyah, Yuli (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2024)
The editorial in this issue highlights Indonesia's position towards Palestine, both from the policies taken by the government and from various publications by Indonesian scholars. The Indonesian government has long tended to support Palestine as an independent country. Historically, before being occupied by Israel, Palestine has supported Indonesian independence, and Indonesia has consistently supported Palestinian independence efforts. Academically, several publications from Indonesian scholars have highlighted many aspects of Palestinian peace and independence efforts.